INTERGRATIVE HEALTH CARE METHOD BASED ON COMBINED COMPLEMENTARY MEDICAL PRACTICES: REHABILITATIVE ACUPUNCTURE, HOMEOPATHY AND CHIROPRACTIC. - RodrÃguez-van Lier, MarÃa Esperanza; Simón, Luis Manuel Hernández; Gómez, Rosa Estela López; Escalante, Ignacio Peón (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This paper presents a systemic approach to health care with complementary therapies such as rehabilitative acupuncture, homeopathy, and chiropractics through the application of a holistic integrated care method, describing the relationship between the different factors involved in the generation of disease for the preservation of health, highlighting the importance of developing a comprehensive care model to support the preexistent health system in countries such as Mexico, based mainly on traditional practices. A healthcare model has to be multi-faceted and interdisciplinary because it has to bring together several specialties and therapeutic methods to provide quality health care in general to the populace.